2012
DOI: 10.9790/3021-0205984989
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and occurrence of residues of the hormones estriol, 17α- ethinylestradiol and 17β-estradiol in urban water supply by HPLC-DAD

Abstract: Hormones 17α-ethinylestradiol, 17β-estradiol and estriol were analyzed in urban water supply due to the concern about the problem associated with the presence of these compounds in water bodies. The aims of this project were adapt, validate analytical methodology and monitor these hormones in drinking water. Results showed that the limits of detection, linearity, regression coefficients and recoveries were suitable for the method and no contamination was detected in samples analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…The PolarScreen assay was used to test the ligand binding affinity of wt-ER α LBD and its mutants towards different classes of estrogen disrupting compounds. The tested chemical compounds (shown in Figure 4 ) were: the natural ligand 17β-estradiol; its close analog 17α-ethynilestradiol (chosen since it is an emerging pollutant [42] ); tamoxifen, a commercial drug antagonist often detected in surface waters [43] ; and three other compounds with known estrogen disrupting activity and significant presence in the environment, bisphenol-A, 4-nonylphenol and 4-tert-octylphenol [44] . The latter three have micromolar binding affinity whereas the first three have nanomolar affinity for wild type ER [45] .…”
Section: Resultsmentioning
confidence: 99%
“…The PolarScreen assay was used to test the ligand binding affinity of wt-ER α LBD and its mutants towards different classes of estrogen disrupting compounds. The tested chemical compounds (shown in Figure 4 ) were: the natural ligand 17β-estradiol; its close analog 17α-ethynilestradiol (chosen since it is an emerging pollutant [42] ); tamoxifen, a commercial drug antagonist often detected in surface waters [43] ; and three other compounds with known estrogen disrupting activity and significant presence in the environment, bisphenol-A, 4-nonylphenol and 4-tert-octylphenol [44] . The latter three have micromolar binding affinity whereas the first three have nanomolar affinity for wild type ER [45] .…”
Section: Resultsmentioning
confidence: 99%
“…The average annual rainfall varies from 1300 to 1800 mm. Monthly averages indicate that the least rainy months are July and August and the highest rainfall occurring in December and January (Torres et al 2012).…”
Section: Characterization Of the Study Areamentioning
confidence: 99%
“…These first reports resulted in the detection of certain drugs in wastewater from STPs in the USA. Several studies have also revealed the presence of PhCs in bodies of water in many other countries (Sirés and Brillas 2012;Torres et al 2012). Hormones have been detected in wastewater, surface water, and groundwater in various regions around the world in concentrations from nanograms to micrograms per liter (Farré et al 2008;López-Serna et al 2010;Alda and Barceló 2001).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A presença de hormônios femininos em águas superfi ciais, águas subterrâneas, águas resíduárias e até mesmo em águas para consumo humano têm sido relatada em diversos países como Inglaterra, Brasil, Alemanha, Canadá, Itália, Holanda, Estados Unidos e Suécia (DESBROW et al, 1998;LARSSON et al, 1999;TERNES et al, 1999;JONHSON, BELFROID e CORCIA, 2000;KOLPIN et al, 2002;TORRES et al, 2012).…”
Section: Ocorrência De Desreguladores Endócrinos No Ambienteunclassified